The Impact of Consumer Co-Creation on Brand Loyalty: A Structural Equation Modeling Approach - Ahmed Yassin, Sanaa; Hussein Abdullah, Salman (Takaza Innovatix Labs Ltd., 2025)
This study explores the impact of consumer co-creation on brand perception, satisfaction, and loyalty. Given the growing importance of consumer involvement in shaping brand identities, this research employs Structural Equation Modeling (SEM) to examine the relationships between consumer co-creation activities and brand outcomes. The study focuses on a sample of 100 respondents actively engaged in co-creation with brands in the fashion, technology, and FMCG sectors. The findings reveal that higher levels of consumer co-creation significantly enhance brand perception and satisfaction, which in turn positively influence brand loyalty. Additionally, the study shows that brand perception and satisfaction mediate the relationship between co-creation and loyalty, indicating that co-creation not only strengthens the emotional connection between consumers and brands but also contributes to long-term consumer commitment. This research provides valuable insights for marketers seeking to leverage co-creation as a strategy for building stronger, more loyal customer relationships in an increasingly competitive marketplace.